Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Mara Vamos, Pascal's pensées and the Enlightenment: the roots of a misunderstanding Preface by Otis Fellows I. Introduction II. The Pensées: a forgotten book III. The serenely unctuous pensées IV. The riddle of the pensées V. Order VI. The omitted thoughts VII. Structural modifications VIII. Stylistic modifications IX. Conclusion Appendix I. Concordance Appendix II. List of social and political pensées Emita B. Hill, The Role of 'le monstre' in Diderot's thought Part I. Physical monsters in nature I. The problem of the presence of monsters in nature II. Monsters and materialism: the early works III. Monsters and materialism in the Rêve de d'Alembert Part II. Human nature and the moral monster IV. In defense of human nature V. The Neveu de Rameau: a moral monster Part III. Monsters and the monstrous deed in Diderot's aesthetic theory VI. The monster in art Select bibliography